EFFECT OF GRAPE SEED EXTRACT ON REMINERALIZATION OF ARTIFICIAL CARIES: AN IN-VITRO STUDY - M, Rubel; Gm, Prashant; Kumar Pg, Naveen; Vh, Sushanth; Imranulla, Mohamed; Potlia, Ipshita; Mallick, Swati (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Grape seeds are gaining more importance because the Proanthocyanidinsâ€ present in them have excellent anticaries, remineralizing, and antibacterial properties. Although many preventive measures have been tried, dental caries remains one of the most prevalent diseases in humans. The ultimate goal of any intervention is the preservation of tooth structure, prevention of lesion progression and inducing remineralization. The present in-vitro study was done to investigate the effect of grape seed extract (GSE) on artificial enamel caries in human teeth. Methods: A total of 50 sound premolars extracted from patients undergoing orthodontic treatment were used in the study. The teeth were cleaned and were immersed in a demineralizing solution for 96 hrs at 37Â°C and 50% relative humidity to create artificial lesions. The samples were randomly divided into two groups of 25 each. Half of the samples were immersed in the GSE solution (test) and the other half in saline (control), respectively, for 8 days. The samples were measured by microhardness tester to obtain values in Vickers hardness scale. Data were entered into Microsoft Excel and were analyzed using independent t-test for inter-group comparison and paired t-test for intra-group comparison using SPSS version 21. Results: The meanÂ±SD microhardness values after remineralization for the test and control groups were 357.56Â±5.53 and 337.60Â±6.38. GSE group significantly increased the microhardness of the lesions (pâ‰¤0.001). Conclusion: GSE is a potential remineralizing agent and can be used to prevent progression of dental caries. Keywords: Grape seed extract, Remineralization, Dental caries.